2021
DOI: 10.1038/s41529-021-00155-8
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation behavior of Cr-coated zirconium alloy cladding in high-temperature steam above 1200 °C

Abstract: Dense, uniform, and well-adhered chromium (Cr) coatings were deposited on zirconium (Zr) alloy claddings by using physical vapor deposition (PVD). The Cr-coated samples were tested at 1200 oC and 1300 oC, respectively, for different exposure time in water steam environment. Microstructures and compositions of the coating/substrate system after oxidation were characterized by X-ray diffraction, scanning electronic microscopy, and energy dispersion spectrometer. The microstructural results clearly demonstrated t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(16 citation statements)
references
References 36 publications
1
10
0
Order By: Relevance
“…10 times longer than current LOCA criteria). Ma et al showed that Cr coatings could protect Zr-1Nb alloy from HT steam oxidation at 1200 and 1300 • C (Figure 5) [95]. It was shown that the thickness of the formed Cr 2 O 3 and residual Cr layers depends on oxidation time, which is probably due to the combined effect of the ongoing redox reactions between chromium oxide and zirconium, also observed by Han et al [96].…”
Section: Chromium-based Coatingsmentioning
confidence: 69%
See 1 more Smart Citation
“…10 times longer than current LOCA criteria). Ma et al showed that Cr coatings could protect Zr-1Nb alloy from HT steam oxidation at 1200 and 1300 • C (Figure 5) [95]. It was shown that the thickness of the formed Cr 2 O 3 and residual Cr layers depends on oxidation time, which is probably due to the combined effect of the ongoing redox reactions between chromium oxide and zirconium, also observed by Han et al [96].…”
Section: Chromium-based Coatingsmentioning
confidence: 69%
“…Optical and SEM images of Cr-coated zirconium alloy cladding after high-temperature steam oxidation at 1200 °C for 0.5 h (a), 1 h (b), 2 h (c), 4 h (d), and 1300 °C for 0.5 h (e) and 1 h (f). Reproduced from[95].…”
mentioning
confidence: 99%
“…However, at elevated temperatures and pressures, this passive oxide layer continues to grow up to a critical thickness, beyond which the protective tetragonal phase transforms into a rapidly growing non-protective monoclinic oxide phase [16][17][18]. The unstable oxide growth causes internal stresses and crack formation, eventually resulting in coating breakdown and corrosion The main advantages of coated cladding [19] include:…”
Section: Introductionmentioning
confidence: 99%
“…The appearance of water side corrosion of the fuel cladding and hydrogen uptake in the cladding at high burnup are the main limitations to burnup extension of nuclear fuel [19].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation